ISOLASI DAN IDENTIFIKASI JAMUR PASCAPANEN PENYEBAB BUSUK BUAH PISANG AMBON (Musa paradisiaca L.) - Setiawati, Rina Agus; Rahmawati, Rahmawati; Wardoyo, Elvi Rusmiyanto Pancaning (Jurnal Protobiont, 2020)
Ambon banana fruit which is attacked by fungi that cause rot does not last long during storage. This study aims to determine the genus of fungi isolated from ambon. The study was conducted at the Microbiology Laboratory, Faculty of Mathematics and Natural Sciences, Tanjungpura University, Pontianak. There were 9 fungal isolates obtained, genus Aspergillus (3 isolates), genus Colletotrichum (1 isolate), genus Fusarium (3 isolates) and genus Penicillium (2 isolates) with the isolates code Aspergillus sp. PA1, Aspergillus sp. PA2, Aspergillus sp. PA3, Colletotrichum sp. PA4, Fusarium sp. PA5, Fusarium sp PA6, Fusarium sp. PA7, Penicillium sp. PA8 and Penicillium sp. PA9.